Data Mining on 5G Technology IOT (International Journal of Engineering and Computer Science, 2019)
Data Mining on 5G Technology IOT Currently, data mining is regarded as one of the essential factors for the next generation of mobile networks. Through research and data analysis, there are expectations that complexity of these networks will be overcome and it will be possible to carry out dynamic management and operation activities. In order to full comprehend the particulars of 5G network, there are certain kind of information that should be gathered by network components in order to be analyzed by a data mining scheme. The recent years have seen a tremendous effort put in the course of designing the 5th Generation of mobile networks (5G). The innovation of 5G mobile networks have been aimed at providing tailor cut solution for different kinds of industries particularly the telecommunication sector, intelligent transportation industries, health sector and even in smart factories. On the other hand, the scientific community has realized that big data solutions can significantly enhance the operation and management of both current and future mobile networks. Usually, data mining is employed in the course of discovering patterns and relationships between different variables particularly in large data sets. Through the use of statistical analysis, machine learning and artificial intelligence are used in the data set in the course of extracting necessary knowledge from the examined data. Data mining is integral in 5G technology because it is through data mining that 5G is considered different particularly through the ease in decision making process that has been offered by the system in order to mitigate some common challenges through a dynamic and proactive mechanism.